Effect of eastward moving cloud clusters over northwest India and neighbourhood on the Indian summer monsoon - LAL, ASOI; SUNDER , R. S.; JOSHI, S. P. (MAUSAM, 1999)
A number of studies have been made relating to the prediction of date of onset and also the activity of southwest monsoon over India. In this study an attempt has been made to link the behaviour of rainfall in northern and peninsular India to the satellite cloud clusters over the region of Afghanistan, Iran and northwest India. The monsoon rainfall over India commences in June. Hence variation of monsoon rainfall pattern with the movement of cloud clusters from northwest in pre-monsoon and monsoon months have been studied to elucidate the pattern of changes. The variability of monsoon performance largely depends on the number and movement of cloud clusters over northwestern region during pre-monsoon and monsoon months.